DEVELOPMENT OF THE DESIGN SCHEME OF THE COMBUSTION CHAMBER FOR BURNING OF WOOD CHIPS THE OLD SLEEPERS - G. I. Pavlov; A. I. Akhmetshina; A. N. Sabirzyanov; A. A. Tikhonov (Известия высших учебных заведений: Проблемы энергетики)
А calculation scheme for the utilization of chips of old wooden sleepers in a vortex furnace is proposed. The vortex furnace provides two zones of reaction of a combustible substance with air: the primary zone is the gasification of old sleepers and the afterburning of the solid residue with a lack of air oxygen, the secondary zone is the burning of the gas phase. The initial data for the thermodynamic calculation is given. The results of the equilibrium calculation of the thermal decomposition of wood on the grate and the combustion of gasification products are presented for different values of the excess air factor, as well as some experimental data. A comparison of the calculation results with the experimental data is carried out.